Improving the Quality of Life During Perimenopause Through Knowledge-Based Education - Levi Tina Sari; Maria Ulfa; Handayani Handayani; Ika Agustina; Maratus Sholichah Fitriah Hajar Kusnianto; Ita Noviasari; Laily Prima Monica; Wahyu Wibisono; Joel Rey Ugsang Acob (Journal of Community Service for Health, 2025)
Perimenopause is a natural process in a woman's life that occurs between the ages of 45 and 55 years. In the context of perimenopause, the quality of life of perimenopausal women is greatly influenced by their ability to understand and manage the biological changes that occur. Knowledge-based education has emerged as a strategic approach to improving the quality of life of perimenopausal women. The stages of implementing community service were the preparation stage, implementation stage and evaluation stage. The community service was done in collaboration between STIKes Patria Husada Blitar Indonesia dan Visayas State University Philippines as the implementation of MOU between schools and the application of the three pillars of higer education in Indonesia. There were 30 participants who entered perimenopause. The data analysis used paired sample t-test. The paired sample t-test showed a p-value of 0.000 < α0.05, indicated a difference before and after the educational intervention. The correlation value between the variables was 0.991, indicated a strong and positive correlation of the community service participants demonstrated a better understanding of general perimenopause knowledge, symptoms and impacts, treatment and prevention, and perimenopause quality of life. This increase in knowledge showed that education had an important role in helping women understand the physiological conditions they experienced. Education gives them the ability to take more adaptive and healthy actions, thus having a positive impact on their physical and psychological well-being.